Agricultural growth in Brazil in the period 1999-2004: Outburst of soybeans and livestock and its iImpact on the environment - Antonio Salazar P. Brand\~ao; Gervásio Castro de Rezende; Roberta Wanderley da Costa Marques (Institute for Applied Economic Research (ipea), 2015)
This paper analyses the Brazilian agricultural growth since January 1999, when a new exchange rate policy was adopted by the country. The analysis focuses on the behavior of the exchange rate and international commodity prices throughout the period 1999-2004. It is also analysed the behavior of cropped area in this recent period, with the conclusion that there has been a fast increase in area planted with grains in the agricultural years 2001/2002, 2002/2003 and 2003/2004, due almost entirely to the growth of soybeans area. The paper proposes that this expansion of area planted with soybeans was based preponderantly on the conversion of pastures. It is also suggested that expansion of soybeans should not be seen as antagonistic to the environmental policy, specially in what respects the protection of the Amazon forest.
Keywords: Q18; 330